Vehicle-augmented evacuation integer programming model for improving safety and efficiency in underground mines - Frimpong Kwaku Asare; Amin Moniri-Morad; Peter Chidi Augustine; Javad Sattarvand (Journal of Safety Science and Resilience)
Ensuring the safe evacuation of miners during fire emergencies in the shortest possible time is one of the most critical aspects of underground mining operations. Despite advances in mining evacuation methods, little research has been conducted on mine vehicles in this context. This study proposed a vehicle-augmented evacuation integer programming (VEIP) model to minimize the total evacuation cost as a function of the required evacuation time during fire emergencies. This approach aims to minimize the risk of miners being exposed to dangerous fire conditions by strategically integrating mine vehicles into the evacuation procedure. The approach determines the optimal evacuation path for each miner, considering factors such as available mine vehicles, miners’ locations, refuge chambers, and fresh-air bases. To validate the effectiveness of the developed VEIP model, a case study was conducted using the mine layout of the Turquoise Ridge Underground Mine in the United States. Furthermore, a statistical comparison was conducted between the VEIP model and the evacuation integer programming (EIP) model, tailored to evacuation on foot, to emphasize vehicles' influence on the evacuation process. The results showed that integrating mine vehicles into evacuation procedures significantly reduces the total evacuation time. A cost savings analysis in the VEIP model revealed that the evacuation time savings increase exponentially as the number of miners present during evacuation increases. The potential benefits of using mine vehicles to improve the efficiency of evacuation from underground mine fires were highlighted in this study.